2003
DOI: 10.1161/01.str.0000069160.05292.41
|View full text |Cite
|
Sign up to set email alerts
|

Lipoprotein Lipase ( LPL ) Gene Variation and Progression of Carotid Artery Plaque

Abstract: Background and Purpose-Coding single nucleotide polymorphisms (cSNPs) in the lipoprotein lipase (LPL) gene have been associated with lipoprotein phenotypes and vascular disease risk. We studied the association between LPL cSNPs and a novel noninvasive measure of disease, namely, cross-sectional carotid plaque area (CPA) on B-mode ultrasound. Methods-Four hundred fifty-two patients from an atherosclerosis prevention clinic had determinations of baseline and total CPA. Traditional atherosclerosis risk factors we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
1

Year Published

2005
2005
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 49 publications
1
35
1
Order By: Relevance
“…There have been inconsistent observations made with regards to the allelic frequencies of the S447X polymorphism of the LPL gene. The frequencies for the S447X range from 4.4% in London [27] to 14% in the Mediterranean population [28]. The HuGe meta-analysis [29] reported a frequency of 9.9% for the 447X allele, with this mutation being more common in East Asians (12.2%) than Caucasians (10.3%), and is in keeping with our study findings (13%).…”
Section: Discussionsupporting
confidence: 89%
“…There have been inconsistent observations made with regards to the allelic frequencies of the S447X polymorphism of the LPL gene. The frequencies for the S447X range from 4.4% in London [27] to 14% in the Mediterranean population [28]. The HuGe meta-analysis [29] reported a frequency of 9.9% for the 447X allele, with this mutation being more common in East Asians (12.2%) than Caucasians (10.3%), and is in keeping with our study findings (13%).…”
Section: Discussionsupporting
confidence: 89%
“…In association studies, although the X447 allele has been reported to be associated with a favorable lipid profile in some studies [7][8]22] the results have not been confirmed in other studies [15]. Similarly, the association of the S447X polymorphism with CAD is inconsistent [10][11][12][13][14][15][16][17][18]. In a meta analysis the association of the S447X polymorphism with TG/HDL-C and CAD was found to be small compared to three other LPL amino acid polymorphisms examined [23] or it was gender-specific [24].…”
Section: Introductionmentioning
confidence: 99%
“…Several common LPL genetic variants have been widely studied, and among them HindIII in intron 8 (T→G at position 481), and S447X in exon 9 are of particular interest because of their common occurrence (25% and 9% of the less common alleles, respectively in most populations) and their associations with plasma lipid profile [6][7][8][9][10][11] and susceptibility to CAD [10][11][12][13][14][15] in several studies, although some inconsistent results have also been reported [16][17][18]. Since the HindIII polymorphism is located in the middle of intron 8, it is not considered to be functional but rather in linkage disequilibrium with a putative functional variant.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, precise measurements of distances, which we have proven to be feasible with Curefab CS, are a necessary condition for satisfactory application of planimetrics as the following step, which is currently the standard method for manual measurement of carotid plaque volume. Acquisition of plaque volume for monitoring carotid atherosclerotic burden therefore seems to be an achievable prospective aim with Curefab CS, and there are a multitude of previous studies showing that volume measurements and morphological characterization of carotid plaques are highly promising for non-invasive risk-stratification and genetic research [10,11,16,34] as well as evaluation of a patient's response to therapy [12,13] .…”
Section: Discussionmentioning
confidence: 99%
“…Despite its usefulness for noninvasive plaque imaging of the carotid arteries, risk stratification and genetic research [10,11] , evaluation of response to antiatherosclerotic and antihypertensive therapy [12,14] and evaluation of the influence of suspected risk factors [15,16] , the modality of three-dimensional ultrasound has not yet been established as a routine diagnostic tool on ultrasound machines. One possible explanation for this may be the fact that images of the carotid arteries comprise a scanning length of at least 4 cm, so that real-time 3-D systems cannot be used satisfactorily [1] .…”
Section: Introductionmentioning
confidence: 99%